IMPROVING THE PSYCHOLOGY OF LEADERS IN PUBLIC ADMINISTRATION (IN THE CASE OF MILITARY PERSONNEL) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article describes the psychology of leadership in military personnel and its specific aspects.